Preface - Brafman, Ronen; Geffner, Hector; Hofman, Joerg; Kautz, Henry (Proceedings of the International Conference on Automated Planning and Scheduling, 2010)
This volume contains the papers accepted for presentation at ICAPS 2010, the Twentieth International Conference on Automated Planning and Scheduling, held in Toronto, Ontario, Canada, May 12–16, 2010. The annual ICAPS conference series was established in 2003 through the merger of two pre-existing biennial conferences, the International Conference on Artificial Intelligence Planning and Scheduling (AIPS) and the European Conference on Planning (ECP). ICAPS continues the traditional high standards of AIPS and ECP as an archival forum for new research in the field of automated planning and scheduling.